GREENER REPORTS, CLEANER BOOKS? THE IMPACT OF SUSTAINABILITY DISCLOSURES ON EARNINGS MANAGEMENT IN ASEAN’S DEVELOPING ENERGY SECTOR - Ari Novalisa Ramadanti; Dyah Febriantina Istiqomah (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
Financial reports represent a form of corporate accountability to stakeholders used for decision-making and evaluating management performance. However, users often focus solely on profit figures without understanding the underlying processes, creating opportunities for management to engage in earnings management practices. These practices can be minimised by disclosing sustainability reports that enhance transparency and reduce information asymmetry between management and stakeholders. This research aims to determine the influence of sustainability disclosure on earnings management in energy sector companies in five developing ASEAN countries (Indonesia, Malaysia, Thailand, Philippines, and Vietnam). The sample was selected using purposive sampling and consisted of 105 companies from 2021 to 2023. Eviews 12 software was used to test the data in this study with an analysis technique using panel data regression. The results of this study indicate that sustainability disclosure influences earnings management. This research encourages regulators to develop more effective and mandatory sustainability reporting policies and standards for the energy sector. Also, it motivates energy companies to improve the quality and quantity of their sustainability disclosure to enhance financial transparency and reduce earnings management practices.